An instrumented approach to quantify wrist and finger flexor spasticity: A study protocol - Anna Pennekamp; Ursula Trinler; Julia Janine Glaser; Mirjam Thielen (PLoS ONE, 2025)
Spasticity in the upper limb is a common condition observed in individuals with Cerebral Palsy, post-stroke or following traumatic brain injury. Affected patients present with significant functional and care challenges. Advances in both conservative and surgical treatments necessitate improved assessment tools. This study aims to develop and validate an instrumented measurement procedure combining 3D motion analysis, surface electromyography (sEMG), and musculoskeletal modeling to assess wrist and finger spasticity and function. The goal is to create a preoperative assessment tool for surgical strategy determination and a postoperative outcome measurement. We hypothesize that this combination of technologies will offer superior assessment accuracy compared to traditional methods and provide predictive insights into therapeutical outcomes.